If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) = -2x + 20 Reorder the terms: 5(3 + x) = -2x + 20 (3 * 5 + x * 5) = -2x + 20 (15 + 5x) = -2x + 20 Reorder the terms: 15 + 5x = 20 + -2x Solving 15 + 5x = 20 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 15 + 5x + 2x = 20 + -2x + 2x Combine like terms: 5x + 2x = 7x 15 + 7x = 20 + -2x + 2x Combine like terms: -2x + 2x = 0 15 + 7x = 20 + 0 15 + 7x = 20 Add '-15' to each side of the equation. 15 + -15 + 7x = 20 + -15 Combine like terms: 15 + -15 = 0 0 + 7x = 20 + -15 7x = 20 + -15 Combine like terms: 20 + -15 = 5 7x = 5 Divide each side by '7'. x = 0.7142857143 Simplifying x = 0.7142857143
| -23=5x-2x+7 | | 1/2x^2+x+5=0 | | 1/4(3x+68)=5x | | -5x-10=-10 | | 7(x-3)=4x-6 | | 3/4-2/5 | | 3(2x-1)+x=-39 | | 5(x-4)=5x-10 | | 31+x*x/4=10 | | 9w^2+30=-25 | | (a+5)(3a-2)= | | 16/16-4x=4/2 | | -u=3u^2-2 | | 21*11/3 | | 6(x+4)+32=-2x | | 3x^3+5-x^3+4x= | | 21*3/11 | | 21/3/11 | | (x-2)/3+(x+5)/4=(2x-1)/6-(x+12)/8 | | 2x-1+2x-1=68cm | | x*x+b=a | | 5/8x-7/15 | | a*x+2=z | | 5/x+3/(2x)=-4/3+5/(2x) | | 5/x+3/2x=4/3+5/2x | | 4x+144=444 | | x^3+5x^2+2x-8=1 | | h(t)=-16t^2+12t+40 | | h(t)=-16x^2+12x+40 | | 76-5x=4x+24 | | x^3+8x^2+15x^1=0 | | 14x+14=-42-10x |